CLINICAL EVALUATION OF TRIPLE AND QUADRUPLE HELICOBACTER PYLORI ERADICATION THERAPY IN PEPTIC ULCER PATIENTS WITH DIFFERENT ABO BLOOD GROUP PHENOTYPES - Abdulridha, Manal Khalid; Kutaif, Rana Hussein; Kamal, Yassir Mustafa; Najeeb, Akram Ajeel (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study aimed to examine the pathological changes in gastric mucosa of Helicobacter pylori-infected peptic ulcer patients carrying different ABO phenotypes and to study the response to the 14 days' standard triple therapy and 10 days' quadruple therapy in peptic ulcer patients according to their ABO phenotypes. Methods: Interventional prospective randomized-controlled open-label study was performed on newly diagnosed patients with PUD. The H. pylori-positive patients were allocated into two major study groups in which they are subdivided according to ABO blood group phenotypes: Group 1 received standard H. pylori eradication triple therapy and Group 2 received standard H. pylori eradication quadruple regimen. Patients were monitored after 2 months for successful H. pylori eradication. Results: Chronic active gastritis was significantly high in patients carrying blood Group O phenotype (81.25%), while the atrophic gastritis and intestinal metaplasia were significantly high in patients carrying blood Group A phenotype (25.00% and 16.67%), respectively. 14 days' triple therapy showed significantly lower eradication rate in H. pylori-infected peptic ulcer patients carrying blood Group O phenotype (p<0.01), meanwhile higher response was found among patients with blood Group B. 10 days' quadruple therapy produced a significant high eradication rate in H. pylori-infected patients carrying blood Group O than those with blood Group A (p<0.01), but still both showed lower response compared to that in patients carrying blood Group B and AB phenotypes. Elderly patients showed significantly less healing efficacy than younger patients (p<0.01), and the least healing rate was noticed in female patients after both regimens. Conclusion: Lower eradication rate in H. pylori-infected was noticed in peptic ulcer patients carrying blood Group O mainly than those with other blood groups and particularly those with duodenal Ulceri. 10 days' quadruple therapy showed significant higher eradication rate in H. pylori infection and a better ulcer healing efficacy.